Feminist Literature: The Path of Arab Women's Struggle - Hishmeh, Lina Sh (Current Progress in Arts and Social Studies Research Vol. 9, 2025)
This study monitors the reality of the Arab woman writer. It reveals the extent of creative freedom she enjoys under overwhelming prohibitions, and personal experiences in their confrontation with the repression of taboos, presenting their testimonies and suffering. On the other hand, the study reveals the rebellion and audacity of women writers in telling the manifestations of repression in their literary texts, without hesitation or fear of punishment, to break social taboos and breach prohibitions, especially the sex taboo. This is done despite the pursuit and punishment of some women writers, and the attempts of others to hide behind aliases or withdrawal from creative writing. The study reveals how the woman's literary creativity interacts with the taboos of the forbidden Trinity: politics, religion, and sex. It explores how Arab women writers confront their censorship taboos and have used literature as a tool to resist and challenge. It provides insights into the struggles and triumphs of women authors in a patriarchal society. Since she had a share of the prison as the man's share, she was imprisoned and tortured, it was not unusual to contribute to writing in prison literature, where she adds to her suffering as a prisoner her suffering as a persecuted woman in one text: "Feminist Prison Literature." Feminist literature is the best experience for the woman to extract her rights, restore her deprived freedom through writing, raise her voice, and exercise the freedom of expression that she has been deprived of for so long. She took out her pen and started "talking like Shahrazad", revealing her experiences and desires, and expressing her concerns and pains. In recent years, she is no longer writing to defend what has been stolen from her demanding change and freedom. Writing for her is no longer a defensive device, but an offensive system in which she condemns and retaliates. In her revolutionary feminist narrative, she demonstrated her offensive tendency against all the taboos of the forbidden trinity.